Sleep disorders as independent predictors of taste dysfunction risk - Rongcai Huang; Quanyi Zheng; Juan Dai; Jinfeng Long; Yansong Wang; Junxin Ni (BMC, 2024)
Abstract Objectives This study aimed to investigate the association between sleep disorders and the prevalence of taste dysfunction and the mediation effect of oral microbe in adults over 40 years. Materials and methods Cross-sectional data were utilized from the National Health and Nutrition Examination Survey (2011-2014). Regression models were employed, adjusting for demographic variables and covariates. Subgroup analyses were conducted based on age, sex, ethnicity, and education level. Multiplicative interactions were assessed through likelihood ratio tests. Additionally, the impact of sleep disturbance on the alpha diversity of the oral microbiome was examined using the rank-sum test (significance threshold: p < 0.05). Mediation analysis based on oral microbiota was conducted. Results The analysis included 4869 participants. After adjusting for adjusting for demographic variables and covariates, individuals with sleep disorders exhibited a 36% increased risk of taste dysfunctions compared to those without sleep disorders (OR: 1.36, 95% CI: 1.00-1.84, p = 0.05). Interaction analyses indicated no significant differences between sleep disorders and taste dysfunctions concerning sex, educational level, and age across various models (Crude Model, Model 1, Model 2, and Model 3; p for interaction > 0.05). Furthermore, compared with the non-sleep disorder group, patients with sleep disorders demonstrated decreased numbers of OTUs, Shannon-Wiener indices, and Faith's phylogenetic diversity indices in the oral microbiota (p < 0.05). However, the mediation analysis failed to reveal an indirect effect of oral microbiome on taste dysfunction (p > 0.05.) Conclusion Sleep disorders independently correlate with a higher risk of taste dysfunctions, potentially associated with alterations in oral flora.